Importin-β proteins expression modulation in embryonic stem cells and embryonic fibroblasts of mouse - Sangel, Percival P. (2020)
Importin-β proteins are transport proteins important in the shuttling of cargo proteins by binding to either nuclear localization signal (NLS) or nuclear export signal (NES). This study investigated the in vitro expression modulation of selected importin-βs. Specifically, this study characterized the culture behavior of mouse embryonic stem cells after knockdown of selected importin-β proteins like Cse1L, IPO7, KPNB1, RanBP16, RanBP17, or XPO4. Also, this study assessed the effects of overexpressing RanBP17 or IPO7 during cellular reprogramming of mouse embryonic fibroblasts (MEFs). Results showed that Cse1L and KPNB1 are essential for the viability of mouse embryonic stem cells since knockdown of either one of these proteins resulted in the death of mouse embryonic stem cells. Meanwhile, the growth characteristics of RanBP17, XPO4, IPO7, or RanBP16 knockdown mouse embryonic stem cells were comparable with the control. Aside from round colonies, the appearance of flat cells and spreading growth characteristics in some colonies were observed, which indicated early signs of differentiation. On the other hand, the number of colonies with overexpressed Oct4, Sox2, Klf4, cMYC (OSKM) + RanBP17, or OSKM+ IPO7 was comparable to OSKM+Flag or OSKM (controls). This suggests that RanBP17 or IPO7 has limited application in the generation of induced pluripotent stem cells. (Author's abstract)